Gamification in ERP systems: A study on intrinsic motivation and user behavioral intentions - ADEBORNA, Esi (Institutional Knowledge at Singapore Management University, 2024)
In the evolving landscape of Enterprise Resource Planning (ERP) systems, integrating gamification shows promise for enhancing user training and education. However, empirical research on gamification's effect on intrinsic motivation in using ERP is limited. Hence, we examined the intrinsic motivational effects of a gamified ERP environment in this research. We created a Gamified Web Application linked to SAP ERP to investigate how gamification affects users' behavioral intention. Leveraging self-determination theory, we examined the influence of perceived competence, autonomy, and relatedness on usage intent. In a controlled experiment with 63 participants, data collected via survey revealed that gamification enhances perceived competence, which substantially influences the intention to use ERP. Additionally, we found that competence fully mediates the relationship between gamification and behavioral intention. This research underscores the role of gamification in addressing the persistent challenge of user adoption by enhancing the perceived competence of users consequently, influencing users' behavioral intentions toward continued use.